FUNCTIONAL-BASED AND ACTIVITY-BASED COST MANAGEMENT SYSTEMS IN WOODWORKING ENTERPRISES- SPECIFICS AND PERSPECTIVES FOR IMPLEMENTATION - Neykov, Nikolay; Trichkov, Neno; Petkov, Angel; Koynov, Daniel (Innovation in Woodworking Industry and Engineering design, 2014)
The role of driver tracing is significantly expanded by identifying drivers unrelated to the volume of product produced. The use of both unit- and non-unit-based activity drivers increases the accuracy of cost assignments and the overall quality and relevance of cost information. Such cost accounting systems are called an activity based cost (ABC) systems. In woodworking exist a great deal of auxiliary processes which require specific costs drivers due to precise the cost allocation. In this paper is made an attempt of modeling and testing of such a methodic for costs tracing and allocation in lumber production.